Towards the emancipation of patients : patients' experiences and the patient movement - Williamson, Charlotte, 1932- (Bristol, UK ; Portland, OR : Policy Press, 2010)
This highly original book examines, for the first time, how the patient movement, which works to improve the quality of healthcare, can actually be considered an emancipation movement when led by its radical elements.
Title from publisher's bibliographic system (viewed on 01 Sep 2022).
Keywords: Patient advocacy; Patient satisfaction; Physician and patient; Medical ethics